2013
DOI: 10.1109/tns.2012.2236358
|View full text |Cite
|
Sign up to set email alerts
|

Source Detection Performance Prediction for a CdZnTe Array

Abstract: Abstract-The complex system response of 3D position-sensitive gamma-ray detectors complicates modeling the recorded measurements and makes exact expressions for detection performance intractable. This makes source detection performance difficult and expensive to compute. Asymptotic analysis has the potential to simplify detection performance prediction with complex systems and has previously been applied to detection performance prediction with simulated gamma-ray detectors. In this work, we use asymptotic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that the performance predicted using (9) agreed well with the empirical performance in the known background case. Additional results with unknown background and background spectrum model mismatch are given in [15].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the performance predicted using (9) agreed well with the empirical performance in the known background case. Additional results with unknown background and background spectrum model mismatch are given in [15].…”
Section: Resultsmentioning
confidence: 99%
“…By using image sequence fusion, we can obtain the all projection information via multi-energy imaging. Multi-energy imaging, such as dual-energy CT, multi-spectrum based on a photon counting detector, can increase the energy spectrum dimension for CT reconstruction, thereby improving the CT quality [9,10]. However, these methods mainly consider material distinction and capture different attenuation relative to the x-ray energy by energy subtraction.…”
Section: Introductionmentioning
confidence: 99%